Nuevas valoraciones críticas a la tradición “Los brujos de Shulcahuanga” - Castillo Sánchez, Wellington (2018)
The paper deals with the new critical assessments of the historical Tradition Los brujos de Shulcahuanga, through a new look at the exegesis, already carried out and, within a holistic approach, of intra, inter and extra textuality, consistent with the nature of the Palmyan Tradition. Locating us in one of its worlds: the historical, (chronic), more than the other: the literary, in which, the Tradition takes its being, and, having achieved its literary values, we try to find objectivity, “proportionality” of the history in the plot of the Tradition, the dimensions and characteristics of a narrated independence uprising, taking care of the inextricable unity of those two worlds, that is given through a language loaded with ironic humor, jocular, satirical and mocking, that conforms the tradition. The findings will allow a comprehensive assessment of the mentioned Tradition.